Cooperação Técnica Internacional e Financiamento Externo: Aportes Teóricos - Oliveira, Marcelo Fernandes de [UNESP] (My University, 2012)
The main objective of this article is to suggest a conceptual taxonomy of thegenerically called International Technical Cooperation (ITC) and Foreign Financial Aid (FFA) phenomena, which will have the pretension to ease their comprehension and their practical consequences for the Brazilian society and for the national State. Insofar, wheninduced by a dynamical structural change in the international society, some Brazilianfederated sectors, specially, municipalities, by the exercise of so-called paradiplomacy or federated diplomacy, are developing public management instruments to acquire resources through ITC and FFA experiences, without making a reflexive thought about their benefits and their consequences.

O objetivo central desse artigo é sugerir uma taxonomia conceitual dos fenômenos genericamente chamados de Cooperação Técnica Internacional (CTI) e Financiamento Externo (FE), a qual terá a pretensão de facilitar sua compreensão e suas consequências práticas à sociedade brasileira e ao Estado nacional.Na medida em que, induzidos por uma mudança estrutural na dinâmica da sociedade internacional, entes federados brasileiros, especificamente os municípios, por meio do exercício da chamada paradiplomacia ou diplomacia federativa, vem elaborando instrumentos de gestão municipal para captar recursos via experiências de CTI e FE, sem efetuar uma reflexão sobre seus benefícios e suas consequências.
International Technical Cooperation and Foreign Financial Aid: Theoretical Contributions
Keywords: Cooperação Internacional; Financiamento Externo